Pengaruh Kepercayaan Dan Promosi Terhadap Minat UMKM Mengambil Pembiayaan Perbankan Syariah Di Kota Langsa - Zikriatul Ulya (Jurnal Manajemen dan Keuangan, 2020)
The purpose of this research is to examine the effect of trust and promotion toward UMKM interest taking islamic banking financing in the city of Langsa. The method used is the quantitative approach. This study uses probability sampling by cluster sampling. The sample used is a small and medium-size micro business in Langsa city of 100 respondents. The data-collection technique a questionnaire by distributing to the small and medium-size microbusiness of Langsa city. Data analysis methods using linear regression, classic assumptions test, and hypothetical test (t and test f). Test t-test results have shown that each independent variable of trust and promotion is partially positive and significant. The results of research on the f show that there is a positive and significant impact together between the trust variables and the promotion of the interest of umkm, which is financing sharia banking in the city of Langsa. Based on the results of the study, it is based on coefficiency analysis, that 50,1 % of the disproportionate value of the people, should be satisfied by the two influential variables, trust and promotion. The remaining 49,9 % is described by other variables not included in the equation.